2019
DOI: 10.1051/0004-6361/201833495
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of mixing-length parameterαfor MLT and FST models by matching with CO5BOLD models

Abstract: Context. Space observations by the CoRoT and Kepler missions provided a wealth of high-quality seismic data for a large number of stars from the main sequence to the red-giant phases. One main goal of these missions is to take advantage of the rich spectra of solar-like oscillations to perform precise determinations of stellar characteristic parameters. To make the best of such data, we need theoretical stellar models with precise near-surface structure, which has significant influence on solar-like oscillatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…The mixing-length parameter was indeed found to vary with evolution and mass (e.g. Freytag et al 1999;Trampedach et al 2014;Sonoi et al 2019). Sonoi et al (2019) showed that the α CGM value can vary from 0.583 to 0.801 for stars with T eff = [4018;6725] K and log g = [1.50;4.50] dex, while the calibrated solar value was 0.69.…”
Section: Impact Of the Mixing-length Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…The mixing-length parameter was indeed found to vary with evolution and mass (e.g. Freytag et al 1999;Trampedach et al 2014;Sonoi et al 2019). Sonoi et al (2019) showed that the α CGM value can vary from 0.583 to 0.801 for stars with T eff = [4018;6725] K and log g = [1.50;4.50] dex, while the calibrated solar value was 0.69.…”
Section: Impact Of the Mixing-length Parametermentioning
confidence: 99%
“…Freytag et al 1999;Trampedach et al 2014;Sonoi et al 2019). Sonoi et al (2019) showed that the α CGM value can vary from 0.583 to 0.801 for stars with T eff = [4018;6725] K and log g = [1.50;4.50] dex, while the calibrated solar value was 0.69. For example, their computations of the mixing-length parameter for a model close to our A8 model gives α CGM = 0.636 (see their Table A.1).…”
Section: Impact Of the Mixing-length Parametermentioning
confidence: 99%
“…In late-type stars, the entropy jump was found to decrease for increasing values of ML2/α (Magic et al 2015). This is because as convection becomes more efficient, smaller temperature gradients in the superadiabatic layers are needed to transport the same flux (Sonoi et al 2019). This relation holds for DB and DBA 1D models where the entropy minimum is located at the top of the He I convection zone (see Fig.…”
Section: Calibration Of the Entropy Jumpmentioning
confidence: 97%
“…where H p is the pressure scale height. This free parameter is not given by the MLT and instead must be calibrated from observations, which is a significant shortcoming of the theory as the particular value of the parameter can have a significant effect on the modelled structures (see examples for both evolutionary and atmospheric models : Shipman 1979;Winget et al 1982Winget et al , 1983Fontaine et al 1984;Tassoul et al 1990;Thejll et al 1991;Bergeron et al 1992;Koester et al 1994;Bergeron et al 1995;Wesemael et al 1999;Córsico & Althaus 2016), especially when convection becomes superadiabatic (Tremblay et al 2015;Sonoi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(2). The Hopf function reads (see Sonoi et al 2019) q(τ) = 1.036−0.3134 exp(−2.448τ)−0.2959 exp(−30.0τ) . (16) In Fig.…”
Section: Intensity Fluctuations In a Grey Atmospherementioning
confidence: 99%